1980
DOI: 10.1002/ajh.2830080212
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant presentation of two chronic leukemias: Evidence for independent clonal evolution

Abstract: A case of chronic lymphocytic leukemia (CLL) occurring simultaneously with Philadelphia chromosome-positive chronic granulocytic leukemia (CGL) in a 58-year-old man is described. The patient presented with typical CGL (all bone marrow mitoses having a Philadelphia chromosome), but during the course of busulfan therapy, CLL became more prominent, less than half of the bone marrow mitoses having a Philadelphia chromosome. The patient is in good clinical condition after a follow-up of 3.5 years, and the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…To our knowledge, the series described in the present retrospective multicentre study is the largest so far reported in the literature: a total of 46 patients affected by CLL/MBL and concomitant MPN, followed by 15 Italian GIMEMA centers were analyzed in this study. In comparison with data emerging from the cases reported in the literature, we observed a lower incidence of CML (19.5% vs. 46.6%) [7–30] and PV (21.7% vs. 32%) [34, 35, 40–53], and a higher incidence of ET (39.2% vs. 21.4%) [31–39] and PMF (13% vs. 1.7%) [54]. In addition, we detected for the first time 3 cases (6.6%) of CLL associated with atypical CML (MPN/MDS).…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…To our knowledge, the series described in the present retrospective multicentre study is the largest so far reported in the literature: a total of 46 patients affected by CLL/MBL and concomitant MPN, followed by 15 Italian GIMEMA centers were analyzed in this study. In comparison with data emerging from the cases reported in the literature, we observed a lower incidence of CML (19.5% vs. 46.6%) [7–30] and PV (21.7% vs. 32%) [34, 35, 40–53], and a higher incidence of ET (39.2% vs. 21.4%) [31–39] and PMF (13% vs. 1.7%) [54]. In addition, we detected for the first time 3 cases (6.6%) of CLL associated with atypical CML (MPN/MDS).…”
Section: Discussionsupporting
confidence: 54%
“…This distribution is similar to what has been reported in the literature, where in roughly one third of cases the diagnosis of MPN was established before, concomitantly or after the diagnosis of CLL (39.4%, 30.3%, and 30.3%, respectively). Most diagnoses of CML both in our series and in the literature followed the diagnosis of CLL (77.7% and 52%, respectively) [18–29], although in our experience none of them occurred simultaneously, in contrast to the 28% of concomitant cases reported in the literature [11–17].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations